Analisis Klaster K-Means Dan Visualisasi Data Spasial Berdasarkan Karakteristik Persebaran Covid-19 Dan Pelanggaran Protokol Kesehatan Di Jawa Tengah - Rosi Anisya Faujia; Muhammad Zidni Subarkah (Seminar Nasional Official Statistics, 2022)
The world is currently faced with the Covid-19 virus pandemic with a significant spike in the spread of cases, especially in Indonesia. The high intensity of the spread of the virus is influenced by the violation of health protocols. In this analysis, the authors took a sample of areas in Central Java using the K-Means Clustering and GeoDa spatial analyze methods with the aim of knowing the characteristics of the spread of Covid-19 in Central Java with indications of health protocol violations. The best number of clusters was obtained, namely 4 clusters with a 74% confidence level. Cluster 1 has the highest confirmed cases of Covid-19. Cluster 2 has the highest health protocol violations. Cluster 3 has the lowest confirmed cases of Covid-19. Cluster 4 had the lowest health protocol violations. The author hopes that this analysis can be a reference for the government to reduce positive number of Covid-19.